Levodopa peripheral pharmacokinetics and duration of motor response in Parkinson's disease. Issue 6 (June 1989) - Kempster, P A; Frankel, J P; Bovingdon, M; Webster, R; Lees, A J; Stern, G M
Abstract : To assess the relative influence of central pharmacodynamic and peripheral pharmacokinetic factors on the duration of motor response to levodopa, the relationship between motor function and plasma levodopa levels was studied in 31 Parkinsonian patients. Duration of benefit from single levodopa doses while fasting depended on the degree to which the plasma levodopa level had declined over four hours; wearing off occurred when the plasma levodopa level had fallen to approximately 50% of peak concentration, irrespective of the duration of the motor response. Whilst the amplitude of motor response to levodopa is likely to be modified by alternations in dopamine receptor stimulation and sensitivity as the disease progresses, it is proposed that the duration of response is primarily determined by levodopa peripheral pharmacokinetics rather than by central pharmacodynamic factors associated with dopamine storage capacity.